Changes in knowledge about law in Hungary in the past half century - Fekete Balázs; Gajduschek György (Sociologija, 2015)
In 1965 Kálmán Kulcsár, the leading researcher of legal sociology carried out the first and for long the last questionnaire survey that aimed to assess the legal knowledge of the Hungarian population. In an omnibus survey representative for the adult Hungarian population we used several questions identical with those of Kulcsár’s in order to answer some of his research question. These questions are for instance: how the knowledge of law (criminal, constitutional, procedural) differs; or how the knowledge level of various social groups (based on gender, age, social status etc.) varies; or how media consumption, civil activity or previous interaction with legal institutions (e.g court) influences knowledge level. Obviously, we had an additional major question: how all these have changed in the past almost half century? Our main finding is that the knowledge about law has certainly increased during this period; moreover, the main impetus behind this was the increase of the general educational level in the country.